Growth and metabolic responses of orange spotted grouper Epinephelus coioides (Hamilton, 1822) fingerlings at different salinity regimes - Xavier, Biji; Megarajan, Sekar; Ranjan, Ritesh; Dash, Biswajit; Sadhu, Narasimhulu; Siva, Ponnaganti; Ghosh, Shubhadeep (Indian Journal of Fisheries, 2021)
A feeding trial was conducted for 60 days to delineate the effect of different salinities on growth and metabolic responses in fingerlings of orange spotted grouper Epinephelus coioides (Hamilton, 1822). The grouper fingerlings (N=1050; Av. wt. 2.0±0.01 g) were distributed equally into seven treatments of varying salinities viz., 5±1‰ (T1), 10±1‰ (T2), 15±1‰ (T3), 20±1‰ (T4), 25±1‰ (T5), 30±1‰ (T6) and 35±1‰ (T7) in triplicates. Fingerlings were fed with commercial diet containing 45% crude protein and 10% lipid. Results from the experiment concluded that growth performance of fingerlings of T4 group was better with minimum metabolic enzyme activity. The liver glycogen was significantly lower (p<0.05) in T4 group. Oxygen consumption rate (OCR) was recorded maximum at 15±1‰ and was significantly reduced for the fingerlings maintained at high salinity (p<0.05) from 20±1 to 35±1‰. Orange spotted grouper fingerlings maintained at salinity of 20±1‰ confirmed that, the animal spent less metabolic energy for maintaining the ionic balance at this optimum salinity compared to other salinities and it was reflected in better growth performance with minimum OCR and metabolic enzyme activities. Keywords: Glycogen, Metabolic enzyme, Orange spotted grouper, Oxygen consumption